Practical Lab-Based Chemistry Learning Using PhET (Physics Educational Technology) Simulation - Yeni Raini; Novi Ayu Safira (Universitas Lampung, 2022)
The Covid-19 pandemic has brought changes in many aspects of life, one of which is learning in schools. This study aims to analyze the use of PhET Simulation (Physics Educational Technology) as an online medium in facilitating chemistry practicum learning at SMA Borces Taruna Terpadu Bogor. Qualitative content analysis was carried out on the acid-base solution material. Data collection techniques in the form of interviews, class and school observation sheets, student response questionnaires, and written tests. The research was carried out in 3 meetings with a time span of 2 x 45 minutes for each meeting and was observed by 1 observer. During the research students are trained operating the PhET platform by researchers and teachers explaining Acid-Base material using PhET simulation in the classroom. Then at the end of the lesson , the students were given a post - test and the distribution of student response questionnaires after using the PhET media. The success of students is assessed from the Minimum Learning Completeness Criteria (KKBM) with a score of 75. The results of the study indicate that using PhET simulation can improve student learning outcomes and activities in carrying out chemistry lab work on acid-base solutions.Keywords : Chemistry Practicum, PhET Simulation, Acid-Base Solution, Virtual Lab